Stability Analysis of a TBM Excavated tunnel at a Critical Section between Main Boundary Thrust and Mahabharat Thrust using RS2 and RS3 - Bohara, Binod; Aryal, Anish; Katuwal, Tek Bahadur; Shilpakar, Pursottam (Journal of Engineering and Sciences, 2025)
This article demonstrates a detailed stability analysis of a tunnel excavated by a Tunnel Boring Machine (TBM) at a critical section between the Main Boundary Thrust (MBT) and Mahabharat Thrust (MT), a case study of Sunkoshi Marine Diversion Multipurpose Project (SMDMP) where double shield TBM was deployed to excavate the tunnel. The geological complexity in this area, including weak rock masses, poses severe challenges to TBM operations. We use the RS2 (2D) and RS3 (3D) numerical modeling software to assess the deformation, squeezing potential, and stress distribution at critical chainage, 4+669m. Rock mass classification based on the Rock Mass Rating (RMR) system was used to determine the quality of the surrounding rock and different empirical methods were applied to estimate rock mass strength and deformability. The results indicate significant deformation at chainage 4+669m, leading to TBM jamming as the installed thrust capacity of the machine was insufficient to overcome the shield friction.